2009
DOI: 10.1080/15424060903167385
|View full text |Cite
|
Sign up to set email alerts
|

Microblogging for Medical Libraries and Librarians

Abstract: Microblogging is the latest and greatest technology to hit libraries and their staffs across the country. Medical libraries, physicians, students, and national health organizations are all starting to utilize microblogging services such as Twitter. This new type of communication is designed to provide its audience with short, to-the-point information, which is in stark contrast to traditional medical documentation processes that are long and often times overly formal and confusing. This article will cover how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The rates of adopting technologies and assessing the value of these new technologies in a library setting are also discussed [1][2][3][4][5][17][18][19][20][21][22][23][24]. No articles simultaneously address what seem to be the three critical facets for designing student-focused library technology projects: device ownership, awareness of software and technology, and willingness to use devices and software to interact with the library.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of adopting technologies and assessing the value of these new technologies in a library setting are also discussed [1][2][3][4][5][17][18][19][20][21][22][23][24]. No articles simultaneously address what seem to be the three critical facets for designing student-focused library technology projects: device ownership, awareness of software and technology, and willingness to use devices and software to interact with the library.…”
Section: Introductionmentioning
confidence: 99%
“…Hricko (2010) uses Tumblr as an example of a microblogging application, as she provides an overview of issues to consider when using microblogs as library tools. Defebbo et al (2009) Tumblr as one of many popular tools for digital librarians to embrace. Mao's (2014) study on the affordances for social media by high school students finds that Tumblr is the third most popular platform among survey respondents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hricko ( 2010) uses Tumblr as an example of a microblogging application, as she provides an overview of issues to consider when using microblogs as library tools. Defebbo et al (2009) focus primarily on Twitter in their article addressing microblogging for medical libraries and librarians but also mention Tumblr as a form of microblogging. Foley et al (2014) explores the use of social networking accounts among future medical students in Ireland and found that Tumblr was used less commonly than Facebook and Twitter.…”
Section: Libraries and Tumblrmentioning
confidence: 99%
“…Kelly et al (2009) identified barriers to the effective deployment of Web 2.0 services to include sustainability risks, digital preservation risks, user disinterest, and accessibility issues. DeFebbo et al (2009) stated the limitations of microblogging to be the very small character limit, a lack of archiving of posts, and a lack of authority. Mincic-Obradovic ( 2009) noted that as anyone can edit the text in a wiki, it "lacks authority and control over its entries, and is prone to vandalism".…”
Section: Impact Of Web 20mentioning
confidence: 99%